ESI, APCI, and MALDI tandem mass spectrometry of poly(methyl acrylate)s: A comparison study for the structural characterization of polymers synthesized via CRP techniques and the software application to analyze MS/MS data. Issue 7 (28th January 2013) - Altuntaş, Esra; Krieg, Andreas; Baumgaertel, Anja; Crecelius, Anna C.; Schubert, Ulrich S.
Abstract Research in polymer science and engineering is moving from classical methodologies to advanced analytical strategies in which mass spectrometry (MS)‐based techniques play a crucial role. The molecular complexity of polymers requires new characterization tools and approaches to elucidate the detailed structural information. In this contribution, a comparison study of poly(methyl acrylate)s (PMA) using different tandem mass spectrometry techniques (ESI, APCI, and MALDI MS/MS) is reported to provide insights into the macromolecular structure with the aid of a special MS/MS data interpretation software. Collision‐induced dissociation (CID) was utilized to examine the fragmentation pathways of PMAs synthesized via various controlled radical polymerization techniques. All three mass spectrometry techniques are used to analyze structural details of PMAs and the labile end‐groups are determined based on the fragmentation behavior in CID. Fragmentation products were identified which are characteristics for the cleavage between the polymer chain and the end‐group. The application of a tailor‐made software is shown to analyze complex MS/MS data, and it is proven that this kind of software will be helpful for polymer scientists to identify fragmentation products obtained by tandem mass spectrometry similar to the fields of proteomics, metabolomics, genomics, and glycomics. © 2013 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2013